Flash card set as rehearse tool for architecture students - Hassanpour, Badiossadat; Che-Ani, Adi Irfan; Şahİn, Nil Paşaoğluları; Tabrizi, Alireza (Open House International Association P.O. Box 74, Gateshead, Tyne and Wear, 2018)
The main goal of architectural education is to increase the independency level of students in finding design solutions throughout their academic years. Despite numerous educational attempts, the lack of supplementary educational methods or tools is still acknowledged by scholars. The present study aims to help students undergo a smooth transition from being highly dependent to minimally dependent on instructors by developing an auxiliary tool that may be used together with critique sessions in design studios. In this study, the critical stages in the design process adopted by students are identified through interviews with instructors and questionnaires for architecture students at Eastern Mediterranean University (EMU) in Cyprus and Universiti Kebangsaan Malaysia (UKM). Basic theories are aligned with the needs and expectations of the chosen case studies to develop a user-friendly model in flash card format. The data analyses show that students and tutors all agree on the two main critical stages of design, namely data analysis and data development (synthesis) which ends with idea simulation. The developed model and the proposed flash cards attempt to connect these critical stages, which are usually skipped by students. Results show that students need to adopt and be equipped with sequences, priorities and creativity techniques in each step of the design process, and the proposed flash cards can help address this concern. © 2018, Open House International Association.
Keywords: Architectural education; Design auxiliary model; Flash card; Independent learning; Students' design pattern